THU0134 Interstitial lung disease and rheumatoid arthritis. multicenter study with tocilizumab. (15th June 2017) - Fernández-Díaz, C; Narvaez-García, J; Martín-Lόpez, M; Rubio-Muñoz, P; Castañeda-Sanz, S; Vegas-Revenga, N; Dominguez-Casas, L; Calvo-Rio, V; Gonzalez-Gay, M; Blanco, R
Abstract : Background: Interstitial Lung Disease (ILD) is a severe extraarticular manifestation of rheumatoid arthritis (RA). AntiTNFα drugs and conventional disease-modifying anti-rheumatic drugs (DMARDs) such as methotrexate (MTX) have been involved in the development of ILD. IL6 has been implicated in the pathogenesis of ILD (Kobayashi J et al). However, a fatal case of exacerbation of ILD has been described with tocilizumab (TCZ) (Kawashiri SY el at). Objectives: Our aim was to assess the efficacy and safety of TCZ in ILD associated with AR. Methods: Multicenter study of RA patients with ILD treated with TCZ. ILD was diagnosed by high-resolution computed tomography (HRCT). TCZ was used at standard dose (8 mg/k/iv/4 weeks). We have analyzed the following variables: a) 1-point change in the degree of dyspnea according to the Modified Medical Research Council (MMRC); b) Forced Vital Capacity (FVC) improvement ≥10%; and improvement ≥10% in DLCO; c) HRCT, and d) joint assessment (DAS28 score). Results: We studied 12 patients (9 women/3 men) with ILD related to RA. The mean age±SD was 57.1±16.1 years. The mean evolution of RA was 9±5.8 years. The patients had previously received the following DMARDs; MTX (n=12), leflunomide (LFN) (8) sulfasalazine (SSZ) (3) hydroxichloroquine (HCQ) (1) azathioprine (AZA) (2), gold salts (2). In addition, 11 patients had previously received biological drugs: adalimumab (4) anakinra: (1), etarnecept (4), rituximab (4), infliximab (1), certolizumab (1), abatacept (1). RA was seropositive in 11 cases (92%). Besides HRCT, the diagnosis of ILD was confirmed by biopsy in 4 patients. In 2 patients ILD was drug-related: MTX (n=2). TCZ was prescribed in monotherapy (n=8) or combined with other DMARDs (4). These DMARDs were: LFN (2), MTX (1), AZA (1). In many patients the dyspnea and DLCO remain stable (Table). After a follow-up of 12 months, 2 patients withdrew TCZ, 1 patient for ILD worsening and 1 patient for joint inefficacy. Conclusions: In our knowledge, this is the largest series that assess the EPID associated with RA treated with TCZ. We observed that in many cases pulmonary involvement remains stable. References: Kobayashi J et al. Chest 1995; 108: 311. Kawashiri SY el at. Rheumatol Int 2012; 32: 4023–6. Disclosure of Interest: None declared